Kinetic and kinematic analysis of hurdle clearance of African and world champion athlete during 110m hurdles: a comparative study - Amara, S.; Mkaouer, B.; Chaabene, H.; Ben-Salah, F. (South African Journal for Research in Sport, Physical Education and Recreation, 2017)
The modelling of athletic movement is an important method in motor-skill learning, which improves the process of teaching and/or training in track and field events. Thus, being a world champion and a world record-holder C.J with the time 12.91 s was chosen as a model-athlete in 110m hurdles in this study. He was compared with R.G, the Tunisian athlete and the African champion based on his personal best of 13.90 s. Consequently, this latter`s biomechanical characteristics were analysed and compared with that of C.J`s. In this regards, the objective of this investigation was to compare the kinematic and kinetic parameters of the 110m hurdle clearance between the two athletes to determine the difference in their hurdling-techniques so that to improve performance. Therefore, R.G`s hurdling sequences over the fourth and fifth hurdle were recorded using four cameras [Sony DCR-PC108E]. His kinematic model was digitized using SkillSpector® software. The results showed a difference in the centre of mass displacement at hurdle clearance and velocity-parameters in both the take-off and the landing phases. When comparing R.G to C.J, this latter proved a smaller vertical displacement and a longer horizontal displacement in addition to a greater horizontal velocity along with a better reaction force, and a higher peak-power. Overall, to improve R.G`s performance, greater horizontal velocity and lower contact time at the take-off phase through a higher rate of force development are needed.